Empirical Evaluation and Combination of Advanced Language Modeling Techniques - Mikolov, Tomas; Deoras, Anoop; Kombrink, Stefan; Burget, Lukas; Cernocky, Jan "Honza" (Interspeech, 2011)
We present results obtained with several advanced language modeling techniques, including class based model, cache model, maximum entropy model, structured language model, random forest language model and several types of neural network based language models. We show results obtained after combining all these models by using linear interpolation. We conclude that for both small and moderately sized tasks, we obtain new state of the art results with combination of models, that is significantly better than performance of any individual model. Obtained perplexity reductions against Good-Turing trigram baseline are over 50% and against modified Kneser-Ney smoothed 5-gram over 40%.